Efek Terapi Citicoline terhadap Pemulihan Kognitif dan Motorik Pasien Stroke Iskemik Akut dengan Polimorfisme ApoE4 rs429358 dan rs7412 - Faizal Muhammad; Afifah Syifaul Ummah; Farida Aisyah; Rivan Danuaji; Subandi; Diah Kurnia Mirawati (Cermin Dunia Kedokteran, 2023)
Citicoline has a neuroprotectant effect, especially in mild-to-moderate stroke. The presence of the ε4 allele in the ApoE gene is associated with a severe acute ischemic stroke (AIS) phenotype, in addition to neurodegenerative risk This study aims to determine the effect of citicoline on cognitive and motoric recovery in severe AIS biomolecularly, such as ApoE4 rs429358 and rs7412 polymorphisms. A 64-year-old woman was diagnosed with AIS with a 6-hour onset and with a NIHSS score of 25 and MMSE score of 21. The patient’s AIS was biomolecularly severe as proven by PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) ApoE4 which yielded 482 bp at rs429358 (codon 112) and 249 bp 167 bp at rs7412 (codon 158) on electrophoretic visualization. The patient received 3x 500 mg intravenous citicoline for 4 days followed by another 1000 mg of citicoline intravenous during polyclinic control for 5 consecutive days. On the 9th day, the patient experienced improvement in cognitive function with an MMSE score of 29 and superior (4/5) and inferior (5/5) motoric strength. Citicoline is a neuroprotectant agent that is beneficial for the recovery of cognitive and motoric function in biomolecularly severe SIA (ApoE4, C/C, Arg112/Arg158) because it can save the penumbra area from infarction.